Transitions in Mathematics Education - Gueudet, Ghislaine; Bosch, Marianna; diSessa, Andrea A; Kwon, Oh Nam; Verschaffel, Lieven (ICME-13 Topical Surveys, 2016)
This book examines the kinds of transitions that have been studied in mathematics education research. It defines transition as a process of change, and describes learning in an educational context as a transition process. The book focuses on research in the area of mathematics education, and starts out with a literature review, describing the epistemological, cognitive, institutional and sociocultural perspectives on transition. It then looks at the research questions posed in the studies and their link with transition, and examines the theoretical approaches and methods used. It explores whether the research conducted has led to the identification of continuous processes, successive steps, or discontinuities. It answers the question of whether there are difficulties attached to the discontinuities identified, and if so, whether the research proposes means to reduce the gap - to create a transition. The book concludes with directions for future research on transitions in mathematics education.